A pilot study of synergy-based FES for upper-extremity poststroke rehabilitation. (29th May 2022) - Niu, Chuanxin M.; Chou, Chih-Hong; Bao, Yong; Wang, Tong; Gu, Lin; Zhang, Xiao; Cui, Lijun; Xuan, Zhi; Zhuang, Cheng; Li, Si; Chen, Zhi; Lan, Ning; et al.
Highlight: Poststroke Fugl-Meyer scores improved more with synergy-based FES compared to Sham. Abstract: A previous study indicated that synergy-based functional electrical stimulation (FES) may improve instantaneous upper-limb motor performance for stroke survivors. However, it remains unclear whether the improvements will sustain over time to achieve functional gains associated with a task-oriented training (TOT). This pilot study was designed to investigate whether there is any promising sign of functional benefits. A TOT protocol with repeated forward and lateral reaching movements assisted by synergy-based FES was conducted in 16 patients (9 FES, 7 Sham) with post-stroke hemiparesis. FES stimuli were applied to 7 upper-extremity muscles of elbow and shoulder during patient movements. Envelopes of stimuli were individualized by re-composing the muscle synergies extracted from a healthy subject. After a five-day training for one hour each day, synergy-based FES induced higher increases in Fugl-Meyer scores (6.67 ± 5.20) than did the Sham (2.00 ± 2.38, p < 0.05). Peak velocity of forward reaching movements increased with a slope 73% steeper in FES group than Sham. In lateral reaching movements, the change in synergy similarity correlated with the change in elbow flexion for the FES group, but not the Sham group. Our results indicate that synergy-based FES therapy induced clinically traceable signs of improvements in poststroke motor performance. The muscle activation in patients also showed promising sign of alteration by FES. Results suggest that a larger scale clinical trial of synergy-based FES may be feasible towards an individualized therapeutic regimen.